Uma arquitetura de Cloud Robotic baseada em clones para uma equipe de CellBots - Pereira, Diego da Silva (2016)
This work about the implementation of an ad hoc communication architecture for a Cellbots team as infrastructure to allow the use of cloud computing. Cellbots are robots that have a financial low cost because they use smarthphones as a central control unit and require few electronic components for their construction. The goal is to expand the horizons of applications for these devices through an architecture that enables communication between robots, allowing them to work as a team, cooperatively, like a Multi-Robot System (MRS), performing di erent tasks, such as searching objects. Another objective of the proposed architecture is to provide the Cellbots the use of resources from cloud computing, treated in the literature as Cloud Robotics.The expected results is to increase the overall capacity of system processing, to enable knowledge sharing and increase automia battery of robots by reduction spending on local processing information. It is proposed a clone based approach in order to achieve the benefits cited with the Cloud Robotics tecnology. The Rapyuta framework was used to instanciete clones and setting up their parameters. To provide communication between robots of the team was adopted the AODV(Ad Hoc On-Demand Distance Vector) protocol. At the end manuscrit some experiments are show to validade the proposed architecture